Population structure of a cave-dwelling bat, miniopterus schreibersii: Does It reflect history and social organization? - Pereira, M. J. R.; Salgueiro, P.; Rodrigues, L.; Coelho, M. M.; Palmeirim, J. M. (Journal of Heredity, 2009)
Many colonial bat species make regional migrations, and the consequent gene flow may eliminate geographic genetic structure resulting from history of colonization. In this study, we verified that history and social organization have detectable impacts on the genetic structure of Miniopterus schreibersii, a cave-dwelling bat with high female philopatry. After studying all known nursing colonies in Portugal, we concluded that there is a significant geographic structure and that the overall pattern is similar for mitochondrial and nuclear DNA. Both pairwise ?ST and FST were significantly correlated with geographical distance, suggesting that isolation by distance is relevant for both mitochondrial and nuclear markers. However, structuring of mitochondrial DNA was much more marked than that of nuclear DNA, a consequence of the strong female philopatry and a bias for male-mediated gene flow. Wintering colonies were more genetically diverse than nursing colonies because the former receive individuals from distinct breeding populations. Haplotype diversity of the northern colonies, the more recent according to population expansion analyses, is only about half of that of the central and southern colonies. This is most likely a consequence of the colonization history of M. schreibersii, which presumably expanded northward from the south of the Iberian Peninsula or North Africa after the last glacial age.